2017
DOI: 10.1038/s41598-017-13889-w
|View full text |Cite
|
Sign up to set email alerts
|

Credit assignment between body and object probed by an object transportation task

Abstract: It has been proposed that learning from movement errors involves a credit assignment problem: did I misestimate properties of the object or those of my body? For example, an overestimate of arm strength and an underestimate of the weight of a coffee cup can both lead to coffee spills. Though previous studies have found signs of simultaneous learning of the object and of the body during object manipulation, there is little behavioral evidence about their quantitative relation. Here we employed a novel weight-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…In the groups that received visual feedback designed to enable external error attribution (Cursor Jump and Hand View), the PDP method shows evidence of explicit learning, as in the Instructed group. Conversely, while external error attribution does not necessarily have to lead to more explicit learning, it seems advantageous to suppress implicit learning when perturbations are external and hence likely to disappear quickly (Berniker and Kording, 2008;Wei and Kording, 2009;Wilke et al, 2013;Kong et al, 2017). Consequently, it is easier to revert to non-adapted behavior if adaptation is largely explicit or strategy-based (Ong and Hodges, 2010;Ong et al, 2012).…”
Section: External Error Attribution Reduces Implicit Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the groups that received visual feedback designed to enable external error attribution (Cursor Jump and Hand View), the PDP method shows evidence of explicit learning, as in the Instructed group. Conversely, while external error attribution does not necessarily have to lead to more explicit learning, it seems advantageous to suppress implicit learning when perturbations are external and hence likely to disappear quickly (Berniker and Kording, 2008;Wei and Kording, 2009;Wilke et al, 2013;Kong et al, 2017). Consequently, it is easier to revert to non-adapted behavior if adaptation is largely explicit or strategy-based (Ong and Hodges, 2010;Ong et al, 2012).…”
Section: External Error Attribution Reduces Implicit Processesmentioning
confidence: 99%
“…Large errors not only evoke more explicit learning (Werner et al, 2015;Neville and Cressman, 2018;Modchalingam et al, 2019), but are also believed to lead people to attribute errors as more likely to be caused externally, i.e. not by oneself (Berniker and Kording, 2008;Wei and Kording, 2009;Wilke et al, 2013;Kong et al, 2017). Previous research found that adaptation of reach movements to visual or mechanical perturbations leads to changes in proprioceptive estimates of hand location Henriques, 2009, 2015;Ostry and Gribble, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While it has been shown that motor adaptation leads to both afferent and efferent based changes in hand localization [1,2,4], it is not clear if both changes are entirely implicit, or if either one can be modulated by explicit components of learning. Awareness of the perturbation may lead to experienced errors being assigned to an external source rather than one that is internal, which has been shown to affect adaptation [39][40][41], and thus should not lead to changes in body-based estimates. However, regardless of whether participants are given instructions prior to adaptation, and regardless of whether they exhibit awareness of the perturbation following training, participants did not show any effects of instruction or rotation size on changes in either proprioception or efferent-based hand localization.…”
Section: Hand Localizationmentioning
confidence: 99%
“…These roles we assign to action selection and execution are reminiscent of another canonical distinction in the motor learning literature, between the learning of body versus tool transformations (Heuer 1983;Körding 2008, 2011;Kong et al 2017) giving rise to modifications of an internal representation of the body (body schema) (Kluzik et al 2008;Cardinali et al 2009) and internal representations of tools, respectively (Massen 2013;Heuer and Hegele 2015). Here, our results would suggest that aftereffects in standard cursor rotation experiments reflect a dedicated mechanism that keeps the system calibrated to minor changes in the transformations of the body, and is therefore sensitive to context regarding the state of the body, but not other aspects of the motor environment.…”
Section: Discussionmentioning
confidence: 99%